(untitled) (Archaeologia Adriatica, 2008)
The results are published in this article from excavations in the area south of the passage of the theater and east of the temple. The temple and theater form an integral architectural complex located within the early nucleus of Salona (the Urbs vetus). Excavation began in the mid 19th century, but only after the excavations by the Danish Foundation in 1922 did it become clear that a temple was located on the southern side of the theater. The theater was never excavated completely, and the results of the excavation and reconstruction of the appearance of the temple were published by F. Weilbach in 1933. According to his results, the temple was older than the theater and had 5 annexes. In the last adaptations, the portico in the east had been enlarged to the dimensions of the wings of the portico on the western side. The excavations carried out in 2006 and 2007 showed that the portico on the east was narrower than that on the west. On the eastern side, the portico was covered by a mosaic of white cubes. The mosaic is in poor condition, but from the preserved paving it is clear that it extended parallel to the portico, probably along the entire length. In layer SJ 014 above the mosaic, 29 pieces of coins were found, only 4 of them entire. The most recent coin was of Arcadius (383 – 408). This stratum was completely black and contained soot, ash, glass, pottery, and many iron nails and spikes that evidently belonged to the roof. Judging from the position in which it was found, the coin was probably lost during a fire at the end of the 4th or beginning of the 5th centuries. Above the paving of the portico was found the northern side of an apse and a wall heading towards the south. The apse and wall were built in the drystone masonry technique, and it is hypothesized that they were related to the walls that were found in 1992 above the western side of the portico. They perhaps should be related to the pottery from the 5th and 6th centuries found above the portico.